A PENTINGNYA PERAN ORANG TUA TERHADAP PENDIDIKAN ANAK MENURUT ABDULLAH NASHIH ‘ULWAN: PENTINGNYA PERAN ORANG TUA TERHADAP PENDIDIKAN ANAK MENURUT ABDULLAH NASHIH ‘ULWAN - Alfi Sa'adah, Nur; Inayatul Ilahiyah, Iva (Al Tadib : Jurnal Ilmu Pendidikan, 2024)
The components required to form a rabbani generation are numerous and undeniable. The primary supporting factor is undoubtedly the role of parents. The author uses the views of Abdullah Nashih ‘Ulwan as a foundation to explore how parents play their role in educating children, as discussed in this research. The researcher's choice in seeking completeness of information and various data uses a library research approach with a qualitative method. The method applied by the researcher to gather this data is through searching for documents that refer to the views of Abdullah Nashih ‘Ulwan. The research results indicate that according to Abdullah Nashih ‘Ulwan, the concept of educating children involves teaching through habits, setting examples, giving advice, supervision, and using discipline. Meanwhile, the role of parents in educating children includes responsibilities towards faith education, morals, physical education, rational education (intellect), psychological education (spiritual), social education, and sexual education